Edward Said’s Defense of Arabs and Islam in ‘Orientalism’ (1978) and ‘Covering Islam’ (1997) - BENSAAD, Ahmed; MEHIFER, Farouk; KAIS, Yacine (Faculty of Letters and Foreign Languages Department of English, 2016)
It is historically acknowledged the fact that Islam and the West have had a religious clash. Indeed, ‗Christianity‘ in the profound past, and mainly the US media, in modern life, caused its fuel. However, the researchers‘ piece of study hinges on mainly Said‘s defense of Arabs and Muslims through his famous works ‗Orientalism‘ (1978) and ‗Covering Islam‘ (1997). In doing so, they endeavor to adjust the erroneous image about Islam, which of purely the making of the West. This modest piece will be divided into two major partitions. In the main, it will cover how Edward Said really advocated Arabs and Muslims and why, regarding his Christianity. Still, ‗Orientalism‘ another important work of Said plays a major standpoint to unravel the Western projects. The relevant results beyond this study discussed, in the first stage, the idea that Media and Experts prejudiced unjustly Islam and Arabs only for the sake of their ascendancy over the world like U.S with Israel were and still doing. At second, for arguably Said was a Christian, and defending this religion and Arabic identity, it revealed for the reader that he was advocating them by the means of his famous works, like the ones mentioned, that contained many criticisms, commentaries, and many thoughtful suggestions and solutions given in particular for Arabs and Muslims, but of his patriotic and humanistic drives not for a religious support